A systematic literature review of aggregate production planning (APP): Social and economic perspectives - Wan Yee Leong; Kuan Yew Wong; Ali Anjomshoae (Journal of Industrial Engineering and Management)
Purpose: The intricate interplay between economic dynamism and social cohesion is essential for holistic advancement and enduring societal welfare. This systematic review aims to critically evaluate APP literature with a focus on social and economic aspects. Previous APP studies have primarily focused only on the economic aspects, often overlooking the social aspects, leading to poor social performance and profit drop.